AR-Based SISKOMA Interactive Multimedia for Improving Conceptual Understanding in Junior High School Science - Taufik Ilham S; Meldi Ade Kurnia Yusri; Mutiara Felicita Amsal; Khairul Alfahani (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This study aimed to develop and evaluate SISKOMA, an Augmented Reality (AR)-based interactive multimedia platform designed to improve students’ conceptual understanding of the Human Coordination System in junior high school science learning. The study employed a Research and Development (R&D) approach using the ADDIE instructional design model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research involved 29 Grade IX students at SMPN 32 Padang selected through purposive sampling. SISKOMA was developed by integrating text, narration audio, animations, instructional videos, interactive quizzes, and WebAR-based three-dimensional visualizations within a single instructional environment. The multimedia design was grounded in Mayer’s Cognitive Theory of Multimedia Learning and Sweller’s Cognitive Load Theory. Data collection instruments included expert validation sheets, teacher and student practicality questionnaires, interviews, and pretest-posttest assessments. The results indicated that SISKOMA achieved a very valid classification from media experts (87.88%) and material experts (87.5%). Practicality assessments showed highly positive responses from teachers (90.2%) and students. Effectiveness analysis using the normalized gain (N-Gain) formula produced a score of 0.54, categorized as moderate improvement. These findings indicate that SISKOMA is a pedagogically feasible and practically accessible AR-based multimedia platform capable of supporting students’ conceptual understanding of abstract biological concepts. The study further highlights the importance of pedagogical integration, cognitive load management, and technological accessibility in optimizing AR-supported science learning.